Adjuvant-free, self−assembling ferritin nanoparticle vaccine coupled with influenza virus hemagglutinin protein carrying M1 and PADRE epitopes elicits cross-protective immune responses - Yongqiang Zhao; Shuangshuang Guo; Jia Liu; Yating Wang; Bo Wang; Chun Peng; Enqi Du; Enqi Du; Enqi Du (Frontiers in Immunology)
IntroductionInfluenza viruses pose a significant threat to global public health. Several influenza pandemic outbreaks have had serious economic and public health implications. Current influenza virus vaccines generally provide strain-specific protection and must be rapidly produced annually to match the circulating viruses. Developing influenza vaccines that confer protection against a broad range of viruses will have a positive impact on public health. In this study, we aimed to develop a ferritin-based influenza nanoparticle vaccine with a broad protective spectrum to enhance the immune response against diverse influenza viruses.ResultsWe generated an adjuvant-free, self-assembling nanoparticle vaccine against diverse influenza A viruses. This nanoparticle vaccine displayed multi-antigen targets on the surface of Helicobacter pylori ferritin, which consists of the ectodomain of hemagglutinin of the H3N2 virus and three tandem highly conserved influenza M1 epitopes fused with the universal helper T-cell epitope PADRE, named HMP-NP. HMP-NPs were expressed in a soluble form in the baculovirus-insect cell system and self-assembled into homogeneous nanoparticles. Animal immunization studies showed that the HMP-NP nanovaccine elicited 4-fold higher haemagglutination inhibition (HAI) titers than inactivated influenza vaccine. And neutralization titers induced by HMP-NPs against the H3N2 virus and heterologous strains of the H1N1 and H9N2 viruses were ~8, 12.4 and 16 times higher than inactivated influenza vaccine, respectively. Meanwhile, we also observed that the number of IFN-γ- and IL-4-secreting cells induced by HMP-NPs were ~2.5 times higher than inactivated influenza vaccine. Importantly, intranasal immunization with HMP-NPs, without any adjuvant, induced efficient mucosal IgA responses and conferred complete protection against the H3N2 virus, as well as partial protection against the H1N1 and H9N2 viruses and significantly reduced lung viral loads.DiscussionOverall, our results indicated that the self-assembled nanovaccines increased the potency and breadth of the immune response against various influenza viruses and are a promising delivery platform for developing vaccines with broader protection against emerging influenza viruses and other pathogens.